PENGARUH PERSEPSI WAJIB PAJAK TENTANG KUALITAS PELAYANAN FISKUS TERHADAP KEPATUHAN WAJIB PAJAK DENGAN KONDISI KEUANGAN WAJIB PAJAK DAN PREFERENSI RISIKO SEBAGAI VARIABEL MODERATING (Studi Empiris Terhadap Wajib Pajak Orang Pribadi Di Kota Semarang) (Students' Journal of Accounting and Banking, 2015)
This study aimed to examine the effect of the taxpayer's perception of the quality of service tax authorities on tax compliance. This study also aimed to examine the effect of the taxpayer's financial condition and risk preferences which acts as a moderating variable in the relationship between the perception of taxpayers about the quality of service tax authorities with tax compliance. The population of this study is the individual taxpayer who has a business and casual employees in the city of Semarang. Sampling was done with convenience sampling method with a sample of 107 respondents. The results showed that the taxpayer's perception of the quality of service tax authorities and the financial condition of the taxpayer positive effect on tax compliance, while risk preferences have no effect on tax compliance. Both moderating variables, the taxpayer's financial condition and risk preferences do not affect the relationship between the taxpayer's perception of the quality of service tax authorities with tax compliance. Keywords: Perception of Taxpayers About The Quality of Service Tax Authorities, The Taxpayer's Financial Condition, Risk Preferences, Tax Compliance